Multiple periodic solutions for impulsive functional differential equations with feedback control - Peilian Guo (Electronic Journal of Differential Equations, 2011)
Using the well known Leggett-Williams fixed point theorem, we study the existence of periodic solutions for a class of impulsive functional equations with feedback control. The main results are illustrated with two examples.